Inside ArcView GIS - Hutchinson, Scott (OnWord Press, 2000)
Inside ArcView GIS functions as a detailed description of the software's functionality and as a comprehensive, self-paced tutorial. An essential how-to manual for the novice and indispensable desk-side reference for the experienced user, this edition begins by establishing the conceptual foundation necessary to use all GIS applications efficiently and effectively. Initial chapters focus on mastering the basics of using ArcView GIS 8.3 "out of the box" for querying, thematic classification, and map composition. With these skills, subsequent chapters lead readers to more advanced expertise, such as editing data, extending data using relational databases, performing spatial analysis (including buffering and overlays), and advanced map composition. Throughout the book, the author's unbiased perspective ensures that readers gain first-hand insights into the strengths and weaknesses of their ArcView GIS 8.3 software, as well as knowledge of workarounds and third-party solutions available to enhance their productivity.